When a storm comes up - Fowler, Allan (Chicago : Childrens Press, 1995)
Tells all about rain and storms, showing what can happen during stormy weather.
Includes index.
Appraisal-Science Books for Young People
Booklist
Science Books & Films (A.A.A.S.)
Appraisal-Science Books for Young People, September 1995
Booklist, July 1995
Keywords: Storms -- Juvenile literature; Storms; Rain; Storms; Weather; Readers (Elementary).